Knowledge and Awareness of Breast Cancer; Its Causes, Prevalence and Prevention - Abary, Mohammed Y. S.; Al-Haddad, Mohammed Gameel Ameen; Alkershi, Faheem Ahmed Abduh; Faquih, Abdulgabar Ahmed Ezzy; Alwesabi, Ali Saad Abdo; Areqi, Abdullah Ahmed (International Journal of Science and Research Archive, 2025)
This study employed a descriptive cross-sectional design to determine the knowledge about the prevalence of breast cancer and its associated factors among the population of Al Hudaydah City and its suburbs, Yemen. The study was conducted in Al Hudaydah City and its suburbs from September 2022 to December 2022. The findings of this study revealed that the majority of participants exhibited low levels of knowledge concerning breast cancer and its preventive measures. Furthermore, the results indicated that while 80% of women with breast cancer were aware of breast self-examination (BSE), only 76% practiced BSE. Overall, a notable deficit in knowledge regarding breast cancer, encompassing its etiology, screening methods, and prevention strategies, was observed, with the majority possessing only a moderate level of understanding.